Contextualizing planning and budgeting systems: public sector experience / Anup Chowdhury and Nikhil Chandra Shil - Chowdhury, Anup; Shil, Nikhil Chandra (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This study is about the exploration of planning and budgeting systems in the context of New Public Management initiatives in Australia. A casebased research method was used in developing a fuller understanding of the relative role of the planning and budgeting system in the management of organisational performance. Evidence from the field support that the researched organisation has operated within the context of a range of reformed government policies, strategies and laws. It was also found that the selected organisation had made changes in its structure and operation to achieve cost-efficiency, budget accountability and an improved customer focus in service delivery. The research demonstrated that planning and budgeting systems in the selected organisation are the functions of the New Public Management linked to the key areas of financial management. These findings are consistent with the view that changes to the Australian public sector promoted managerial accountability and a culture of performance. The research undertaken was in-depth, using a case study and though generalisation is not possible, the findings may add knowledge to the existing literature and provide some important lessons for other public sector entities who are interested in adopting these control systems as their control devices.